Truncated titin is structurally integrated into the human dilated cardiomyopathic sarcomere - Kellermayer, Dalma; Tordai, Hedvig; Kiss, Balázs; Török, György; Péter, Dániel M.; Sayour, Alex Ali; Pólos, Miklós; Hartyánszky, István; Szilveszter, Bálint; Labeit, Siegfried; Gángó, Ambrus; Bedics, Gábor; et al. (The journal of clinical investigation, 2024)
Heterozygous (HET) truncating variant mutations in the TTN gene (TTNtvs), encoding the giant titin protein, are the most common genetic cause of dilated cardiomyopathy (DCM). However, the molecular mechanisms by which TTNtv mutations induce DCM are controversial. Here, we studied 127 clinically identified DCM human cardiac samples with next-generation sequencing (NGS), high-resolution gel electrophoresis, Western blot analysis, and super-resolution microscopy in order to dissect the structural and functional consequences of TTNtv mutations. The occurrence of TTNtv was found to be 15% in the DCM cohort. Truncated titin proteins matching, by molecular weight, the gene sequence predictions were detected in the majority of the TTNtv+ samples. Full-length titin was reduced in TTNtv+ compared with TTNtv– samples. Proteomics analysis of washed myofibrils and stimulated emission depletion (STED) super-resolution microscopy of myocardial sarcomeres labeled with sequence-specific anti-titin antibodies revealed that truncated titin was structurally integrated into the sarcomere. Sarcomere length–dependent anti–titin epitope position, shape, and intensity analyses pointed at possible structural defects in the I/A junction and the M-band of TTNtv+ sarcomeres, which probably contribute, possibly via faulty mechanosensor function, to the development of manifest DCM.